2006
DOI: 10.4049/jimmunol.176.6.3374
|View full text |Cite
|
Sign up to set email alerts
|

CTL Adoptive Immunotherapy Concurrently Mediates Tumor Regression and Tumor Escape

Abstract: Tumor escape and recurrence are major impediments for successful immunotherapy. It is well-documented that the emergence of Ag-loss variants, as well as regulatory mechanisms suppressing T cell function, have been linked to inadequate antitumor activity. However, little is known regarding the role of Fas-mediated cytotoxicity by tumor-specific CD8+ CTL in causing immune evasion of Fas resistant variants during adoptive immunotherapy. In this study, we made use of an adoptive transfer model of experimental lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 43 publications
2
38
0
2
Order By: Relevance
“…Treatment of tumor-bearing mice by CTL adoptive transfer was conducted as previously described (23). To inactivate endogenous host immune cells, mice were irradiated in a Gammacell 40 Exactor Radiator (Nordion International) for a total dose of 5 Gy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of tumor-bearing mice by CTL adoptive transfer was conducted as previously described (23). To inactivate endogenous host immune cells, mice were irradiated in a Gammacell 40 Exactor Radiator (Nordion International) for a total dose of 5 Gy.…”
Section: Methodsmentioning
confidence: 99%
“…Spleen-derived CD8 + CTL lines were maintained and propagated in 24-well plates (2 Â 10 Cytotoxicity assay. CTL activity was assessed by 51 Cr release assays as previously described (23). To analyze the role of LThR, lytic assays were done in the absence or presence of anti-LThR mAb (clone AC.H6; PharMingen).…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that antitumour CTL responses in vivo can concurrently mediate tumour regression and tumour progression through the selection and outgrowth of residual Fas lo variants that possess enhanced malignant potential. In fact, such Fas lo variants were not only more aggressive in vivo, but also significantly more refractory to CTL-adoptive immunotherapy (Liu et al, 2005b(Liu et al, , 2006. In addition, in both mouse and human solid tumour models, it was demonstrated that biological selection against Fas-responsive cells within parental or primary tumour cell lines, using surrogate sources of Fas engagement, generated Fas lo sub-populations with enhanced malignant ability (Liu et al, 2003;Liu and Abrams, 2003a (Liu et al, 2005a).…”
Section: Apoptotic Resistancementioning
confidence: 99%
“…Several studies have examined whether an antitumour CD8 þ CTL response actually 'selects' such neoplastic sub-populations with enhanced resistance to Fasinduced death (Liu et al, 2005b(Liu et al, , 2006. These studies revealed that antitumour CTL responses in vivo can concurrently mediate tumour regression and tumour progression through the selection and outgrowth of residual Fas lo variants that possess enhanced malignant potential.…”
Section: Apoptotic Resistancementioning
confidence: 99%
See 1 more Smart Citation